Slow-Time MIMO STAP with Improved Power Efficiency - Mecca, V.F.; Krolik, J.L. (2007 Conference Record of the Forty-First Asilomar Conference on Signals, Systems and Computers, 2007)
This paper concerns a multiple-input multiple- output (MIMO) generalization of space-time adaptive processing (STAP) to mitigate radar clutter subject to multipath propagation between transmit and receive arrays. Slow-time MIMO transmit channels are phase-coded to be orthogonal post-Doppler processing at the receiver (";slow-time";) and are easily implemented without receiver modification before range pulse-compression. Slow-time MIMO STAP methods coherently combine orthogonal received waveforms, steering virtual transmit nulls in cone angles responsible for multipath clutter [1]. A potential problem with MIMO STAP is the occurrence VSWR peaks over the course of a dwell. Herein, we consider sub-array designs that improve power efficiency by reducing VSWR.